The customs law of Asia - Cottier, Michel; Corbier, Mireille (Oxford studies in ancient documents., 2008)
A new edition, with translation, introduction, commentary, and interpretative essays, of the Lex Portorii Asiae - the regulations drawn up over nearly two centuries for the customs dues of the rich province of Asia (western Turkey). - ;The Roman Empire was based on law, and it was vital for rulers and ruled that laws should be understood. They were often given permanent form in stone or bronze. This book transcribes, translates, and fully illustrates with photographs, the inscription (more than 155 lines, in its damaged state) that carries the regulations drawn up over nearly two centuries for.